2015
DOI: 10.3109/10253890.2015.1087505
|View full text |Cite
|
Sign up to set email alerts
|

Sex-dependent effects of chronic psychosocial stress on myocardial sensitivity to ischemic injury

Abstract: Individuals with post-traumatic stress disorder (PTSD) experience many debilitating symptoms, including intrusive memories, persistent anxiety and avoidance of trauma-related cues. PTSD also results in numerous physiological complications, including increased risk for cardiovascular disease (CVD). However, characterization of PTSD-induced cardiovascular alterations is lacking, especially in preclinical models of the disorder. Thus, we examined the impact of a psychosocial predator-based animal model of PTSD on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 42 publications
2
33
0
2
Order By: Relevance
“…subjecting animals to physical restraint, social isolation, predation stress, forced swimming, environmental instability, and randomized series of such stressors), which exhibit symptoms of depression that may include anhedonia and decreases in sexual drive, aggression, investigative behavior and locomotion, together with circadian disruption, disordered sleep and weight loss [38,39] (models discussed below in section 4). These studies identify both ultrastructural disruption in otherwise healthy hearts [40,41] and substantial changes in myocardial injury responses [40,[42][43][44][45][46][47]. However, they have not yet developed a mechanistic understanding of these cardiac outcomes.…”
Section: Pre-ischemic Depressionmentioning
confidence: 99%
See 3 more Smart Citations
“…subjecting animals to physical restraint, social isolation, predation stress, forced swimming, environmental instability, and randomized series of such stressors), which exhibit symptoms of depression that may include anhedonia and decreases in sexual drive, aggression, investigative behavior and locomotion, together with circadian disruption, disordered sleep and weight loss [38,39] (models discussed below in section 4). These studies identify both ultrastructural disruption in otherwise healthy hearts [40,41] and substantial changes in myocardial injury responses [40,[42][43][44][45][46][47]. However, they have not yet developed a mechanistic understanding of these cardiac outcomes.…”
Section: Pre-ischemic Depressionmentioning
confidence: 99%
“…Ravingerova et al found chronic stress also increases contractile dysfunction and risk of post-ischemic arrhythmias in normotensive rats, though stress somewhat paradoxically improved these parameters in hypertensive animals [45]. While emulating posttraumatic stress disorder (PTSD), a more recent study in a psychosocial predator-based animal model reports increases in contractile dysfunction and myocardial death following ischemia, though specifically in males and not females [46]. Delving into mechanistic elements, Rakhshan et al found that chronic physical or psychological stress worsened myocardial damage during infarction, and that this effect was eliminated by chemical sympathectomy (without influencing corticosterone levels) [47].…”
Section: Pre-ischemic Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because previous work with our model of PTSD revealed long-term adverse effects on cardiovascular reactivity (e.g., hypertension), as well as increased levels of inflammation, we explored whether the model would exacerbate myocardial damage following experimentallyinduced ischemia (Rorabaugh et al, 2015). After the 31-day stress paradigm, rats were anesthetized, and their hearts were removed and placed in a Langendorff isolated heart system.…”
Section: Accepted Manuscriptmentioning
confidence: 99%